2012
DOI: 10.1136/archdischild-2012-301885.219
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid supplementation in children with sickle cell disease

Abstract: The aim of our review was to evaluate the evidence for and against folic acid supplementation in sickle cell disease. Folic acid has been both widely prescribed and hotly debated for the last four decades. We undertook an extensive literature based review with the aim of evaluating the clinical benefits of this supplementation and its implications on future paediatric practice. Comprehensive scientific search engines were used to locate articles published up to June 2011. A wide range of search terms were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Concomitant presence of anemia and homocystenemia are well associated with frequent vascular crisis which often lead to altered physical growth of the child particularly in homozygous SCD cases. [21][22][23] Present study showed significant association of A1298C with BMI and anemia grades (p = 0.001). Children with A1298C variants also depicted lower mean for hemoglobin and anthropometric metrics (Table 3).…”
Section: Discussionsupporting
confidence: 49%
“…Concomitant presence of anemia and homocystenemia are well associated with frequent vascular crisis which often lead to altered physical growth of the child particularly in homozygous SCD cases. [21][22][23] Present study showed significant association of A1298C with BMI and anemia grades (p = 0.001). Children with A1298C variants also depicted lower mean for hemoglobin and anthropometric metrics (Table 3).…”
Section: Discussionsupporting
confidence: 49%
“…For this reason, SCD patients commonly take folic acid on the premise that it will replace depleted folate stores and reduce the symptoms of anemia. However, this has not yet been formally demonstrated and is still controversial [19]. In our opinion, folic acid supplementation is required in the DRC.…”
Section: Discussionmentioning
confidence: 89%
“…We are aware of an article by Al Yassin; however, we could not retrieve the full text for the article (abstract only); we have contacted the author for further details, and await their reply (Al-Yassin 2012). From the abstract available we could ascertain that it was a literature review which included only a small number of studies.…”
Section: Agreements and Disagreements With Other Studies Or Reviewsmentioning
confidence: 99%